Natural coagulation for the decontamination of industrial effluents - Banchón, Carlos; Baquerizo, Ricardo; Muñoz, Diego; Zambrano, Leila (Enfoque UTE, 2016)
Industrial and agricultural pollution has generated undoubtedly a high environmental impact on the natural resources of our planet. Deficiencies in the provision of water for human consumption due to pollution from natural sources are expected. In response to this, the application of iron and aluminum coagulants are the first choice for wastewater treatment. However, the abundant use of aluminum is subject of discussion because of the potential impact on humans. Therefore, this article highlights the latest advances in the field of natural coagulation, an ancestral technology used for water decontamination. Its proven effectiveness is based on electrokinetic destabilization mechanisms that remove turbidity up to 99%. Experimental evidence agrees that concentrations of tannins and mucilages allow the remediation of effluents from chemical industries such as textile and tanneries.